Lime/pozzolan/geopolymer systems: Performance in pastes and mortars - Villca, Ariel R.; Soriano, Lourdes; Font, Alba; Tashima, Mauro M. [UNESP]; Monzó, José; Victoria Borrachero, Maria; Payá, Jordi (Elsevier, 2021)
Use of lime as construction material is limited mainly by low initial strength. These properties can be improved by adding pozzolanic materials, but the evolution of the reaction usually needs older ages than 7 days. Alkali-activated materials, or geopolymers, are good-performance materials that can be produced with residual waste. The combination of traditional and new materials can lead to new uses of lime mortars. This paper studies a lime/pozzolan and geopolymer mixture. The chosen pozzolan is fluid catalytic cracking catalyst residue (FCC), a material employed as a precursor in alkali-activated material. FCC is activated by two activators: a mixture of NaOH and waterglass; a mixture of NaOH and rice husk ash (RHA). The new materials were studied in microstructure and mechanical behaviour terms. The results demonstrated that lime/pozzolan/geopolymer obtained superior compressive strengths after 1 curing day to that obtained for the corresponding lime/pozzolan mortar after 90 days. An improvement in compressive strength of around 145% was achieved for the mortar with 40% geopolymer compared to the mortar with only lime/pozzolan at 28 curing days.
Keywords: Fluid catalytic cracking catalyst residue; Geopolymer; Lime; Pozzolan; Waste material